2021
DOI: 10.12688/f1000research.52135.1
|View full text |Cite
|
Sign up to set email alerts
|

Roles and Problems of Stroke Caregivers: A Qualitative Study in Yogyakarta, Indonesia

Abstract: Background: Caregivers play a central role in post-stroke patients care. However, the role of and problems managed by caregivers have not been widely studied, particularly in Indonesia. This study aims to explore the roles and problems of caregivers in post- stroke patients’ care. Method: This was a qualitative study. Caregivers of post-stroke patients from the homecare clinic of Dr Sardjito General Hospital were purposely selected during January 2017 to June 2018. Focus group discussions were conducted to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This demonstrated that, despite the widespread use of the Internet, many caregivers continued to seek information and knowledge in managing stroke patients, which was lacking, incomplete, and difficult to obtain from traditional sources, primarily rehabilitation centers. Previous research found that a lack of specific knowledge and information on the illness and the patient's issues and needs were indeed common issues for family caregivers [37][38][39]. This includes social support, such as the availability of welfare aids, which is commonly associated with a lack of longterm support or stroke aftercare [40] and a perceived lack of attention regarding patients' social recovery [41][42][43], as revealed by this study.…”
Section: Discussionmentioning
confidence: 61%
“…This demonstrated that, despite the widespread use of the Internet, many caregivers continued to seek information and knowledge in managing stroke patients, which was lacking, incomplete, and difficult to obtain from traditional sources, primarily rehabilitation centers. Previous research found that a lack of specific knowledge and information on the illness and the patient's issues and needs were indeed common issues for family caregivers [37][38][39]. This includes social support, such as the availability of welfare aids, which is commonly associated with a lack of longterm support or stroke aftercare [40] and a perceived lack of attention regarding patients' social recovery [41][42][43], as revealed by this study.…”
Section: Discussionmentioning
confidence: 61%
“… 7 , 8 Based on research from the hospital, there are suboptimal services due to limited physiotherapy facilities and resources. 9 In the hospital, physiotherapy is carried out by officers during working hours; then, the staff teaches the family to be able to do it. However, when the patient has returned home, the Range of Motion (ROM) exercise is not carried out by the patient’s family due to the lack of knowledge and family self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the patient has returned home, the Range of Motion (ROM) exercise is not carried out by the patient’s family due to the lack of knowledge and family self-efficacy. 9 It was regarding the concepts and techniques for doing ROM exercises, even though they must be done as early as possible and as often as possible. Not all families can perform ROM exercises on patients after they go home.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations